Unlocking Weather Observations at Puerto Madryn-Patagonia, Argentina, 1902–1915 - Lakkis, Susan Gabriela (2024)
The reconstruction of early records of maximum, minimum and mean temperature, pressure, and relative humidity measurements in Puerto Madryn for the period 1902-1915 is presented. A careful evaluation of the quality of the data was performed using internal coherence, tolerance, and temporal consistency tests. Monthly mean series constructed from daily raw data were subject to several homogeneity tests and discontinuities in pressure and relative humidity were found. The homogenized monthly mean series were compared with the Twentieth Century Reanalysis series, in annual and seasonal time steps. In addition, the trends of each variable were assessed using the Mann Kendall procedure and correlations between relative humidity and the other variables were examined. The results show a remarkably good agreement between the temperature measurements and reanalysis values, with a Spearman correlation coefficient of 0.94. The raw data for minimum and maximum temperature represent a very good upper and lower bound for the mean temperature values of both observational and reanalysis data. Agreement was found lower for relative humidity and pressure, with the correlation coefficients being close to 0.6 in both cases. No trends were found for the variables. The correlation analysis of the humidity measurements with the other variables shows an inverse dependence of the temperatures and no relatedness with the pressure values.